(3GdLGe GdYhGe Yf Yde GdcdGes - (3eMeO Hf eMeO Hf eMeO GdZRGdj GdTGaYj GdWhSj , CHh MGeO, MLI GdGSdGe GdZRGdj,J (B505 (3g` s
(3ChdgG (B:s
(3CeG HYO abO SCdJfi GQTOc Gdgd Yf GdGNHGQ GdehgeI GdJTHjg YfO GdQYGY hGQOJ Gf GTQM dc GYJbGO GdSda hGf fHjf eG jLH Ydi Yehe GdNdb Gf jYJbO s
(3BNQgG (B:s
(3CNQg fGbU hjfJgi HChd GdhXjaI GdKGfjI GdGjeGf hGdJUOjb hgh Gf JYde bWYG UGf gPg GdCdaGX CQjO HgG eYfi jdjb HLdGd Gddg JYGdi hYXeJg hGf QShd Gddg Udi Gddg Ydjg hSde s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B22 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B266 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B79s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B148s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJhMjO hGdedd hGdfMds